ISOLASI DAN IDENTIFIKASI SENYAWA FLAVONOID DALAM DAUN BELUNTAS (Pluchea indica L.) - Koirewoa, Yohanes Adithya; Fatimawali, Fatimawali; Wiyono, Weny (UNIVERSITAS SAM RATULANGI, 2012)
Isolation and identification flavonoid compounds in beluntas leaf (Pluchea indica L.) have beenconducted. Isolation was carried out by using 96% p.a ethanol solvent of maceration extraction for 7days and partition using n-heksana solvent to obtain concentrated beluntas leaf extract. The extractwas purified by thin layer chromatography using eluent n-butanol : asetic acid : water (BAA) (4:1:5).Isolate 3, result from thin layer chromatography contain flavonoid compound. Ultra Violet - Visiblespectra showed that the flavonoid compound was flavonol, with characteristic wavelengths from 250to 280 nm for band II and 350-385 nm for band I.Keywords: beluntas, flavonoid, Thin Layer Chromatography, UV-Vis Spectrophotometer